EFEKTIVITAS PEMBELAJARAN PAI MENGGUNAKAN MEDIA POWER POINT DENGAN VIDEO MUHASABAH DI KELAS 5 SDIT IQRA’ 1 KOTA BENGKULU - Gurniman Sutarno (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2018)
The purpose of this research  is to know the planning,  action and  result or evaluation of the effectiveness  of Islamic Education Lesson Using Power Point Media with Muhasabah Video in the Fifth Grade  of Integrated  Islamic Elementary School IQRA’ 1 Bengkulu.  This research  is an evaluative  research  with descriptive purpose using mixed methodology design. The data was collected  by using observation, interview,  questionnare, and  documentation methodology. In this research, the  method of analysis which is used in discussing the problems  was descriptive  analysis method with triangulation technique. Meanwhile, in quantitative side, the data  analysis  was by tabulating  data  according  to students’  answer.  Furthermore, the researcher in- terprated the data  of each  indicator  researched. The evaluation result of Islamic Education lesson with Power  Point  media  in cognitive aspect was the result of students’ final score report increased 0.7 points. The research  result can be concluded that The Effectiveness of Islamic Education Lesson Using Power Point Media with Muhasabah (red: self introspection) Video in the Fifth Grade  of Integrated  Islamic Elementary School IQRA’ 1 Bengkulu City was categorized  effective